Granting of Dependent Rights: A Legal Comparison Between Indonesia and Malaysia - Saro, Inoto; Pasaribu, Simon Alex; Napitupulu, Diana Ria Winanti (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: The enforcement of security rights plays a crucial role in debt guarantee systems, balancing the interests of creditors and debtors. Although both countries share a civil law tradition, significant differences exist in their execution mechanisms, particularly regarding the role of the courts, auction procedures, and the protection of debtor rights. In Indonesia, execution procedures are governed by Law Number 4 of 1996 on Mortgage Rights, which allows creditors to initiate either a parate execution or litigation through court proceedings. In contrast, Malaysia mandates judicial foreclosure for all mortgage enforcements, as regulated under the National Land Code 1965 and the applicable procedural rules.Purposes of the Research: This study aims to analyze and compare the procedures for executing mortgage objects between Indonesia and Malaysia.Methods of the Research: This research adopts a normative juridical and descriptive-comparative approach by examining statutory regulations, court decisions, and relevant legal literature from both jurisdictions.Findings of the Research: The findings reveal that Indonesia’s system offers speed and flexibility but poses a higher risk of procedural abuse, while Malaysia’s judiciary-based approach provides greater debtor protection at the cost of increased time and legal expenses. The study also identifies practical challenges such as administrative delays, high execution costs, and legal uncertainties. Accordingly, this research recommends strengthening the oversight of execution practices in Indonesia and considering the introduction of a statutory limitation period, as implemented in Malaysia, to ensure a balanced approach between efficiency and justice in mortgage enforcement systems.